2007
DOI: 10.1097/01.fch.0000264880.96310.9a
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Patterns in a Community of Native Hawaiian Mothers Participating in WIC

Abstract: Although Hawaii has high breastfeeding initiation rates (89%), Native Hawaiian WIC* participants have much lower initiation (64%) rates. Little is known about why these disparities occur. The study's aim was to describe the breastfeeding patterns of Hawaiian/part-Hawaiian women enrolled in the WIC who had initiated breastfeeding. Retrospective descriptive data (N = 200) were gathered from WIC records. Descriptive and parametric statistics with univariate and multivariate analysis of breastfeeding patterns were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Despite recommendations and numerous health care benefits attributed to breastfeeding, 5 rates of breastfeeding remain low, particularly within low‐income and some ethnic populations. In Hawaí, the breastfeeding initiation rate is higher (89.6%) than the national average (70.0%), except within Native Hawaiian and Pacific Islander (46.5%) populations 6,7 . Similarly low rates are also found in other US at‐risk populations and have been associated with teen pregnancy, drug abuse, and poverty 6 …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite recommendations and numerous health care benefits attributed to breastfeeding, 5 rates of breastfeeding remain low, particularly within low‐income and some ethnic populations. In Hawaí, the breastfeeding initiation rate is higher (89.6%) than the national average (70.0%), except within Native Hawaiian and Pacific Islander (46.5%) populations 6,7 . Similarly low rates are also found in other US at‐risk populations and have been associated with teen pregnancy, drug abuse, and poverty 6 …”
Section: Introductionmentioning
confidence: 92%
“…In the past, children grew up seeing mothers and family members breastfeeding and had the benefit of family and community support. Currently many extended families are fragmented; if mothers and grandmothers are available, they may not have breastfed 6,8 . The provision of ongoing support has been shown to increase the proportion of women who continue to breastfeed for up to 6 months 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of NHOPI women was very small (n = 15) and the wide confidence interval suggests that a larger sample size may be needed to produce a more precise estimate of effect. Other studies have reported lower rates for breastfeeding discontinuation in NHOPI women in Hawaii (Dodgson et al 2007), although, in comparison to other races, the percentages of NHOPI women who discontinued breastfeeding were higher. A small study of postpartum Native Hawaiian women in Hawaii enrolled in WIC during 2003–2005 reported that 48% of the women discontinued breastfeeding before 6 months postpartum (Dodgson et al 2007).…”
Section: Discussionmentioning
confidence: 70%
“…Other studies have reported lower rates for breastfeeding discontinuation in NHOPI women in Hawaii (Dodgson et al 2007), although, in comparison to other races, the percentages of NHOPI women who discontinued breastfeeding were higher. A small study of postpartum Native Hawaiian women in Hawaii enrolled in WIC during 2003–2005 reported that 48% of the women discontinued breastfeeding before 6 months postpartum (Dodgson et al 2007). According to the 2014 PRAMS, 28% of low-income NHOPI women in Hawaii who initiated breastfeeding discontinued breastfeeding before 8 weeks postpartum (“Hawaii IBIS Query Builder Hawaii’s Pregnancy Risk Assessment Monitoring System Data,” n.d.).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation